Cognitive Ameliorating Effect of Acanthopanax koreanum Against Scopolamine‐Induced Memory Impairment in Mice. (6th February 2017) - Lee, Sunhee; Park, Ho Jae; Jeon, Se Jin; Kim, Eunji; Lee, Hyung Eun; Kim, Haneul; Kwon, Yubeen; Zhang, Jiabao; Jung, In Ho; Ryu, Jong Hoon
Abstract : Acanthopanax koreanum Nakai (Araliaceae) is one of the most widely cultivated medicinal plants in Jeju Island, Korea, and the roots and stem bark of A. koreanum have been traditionally used as a tonic agent for general weakness. However, the use of A. koreanum for general weakness observed in the elderly, including those with declined cognitive function, has not been intensively investigated. This study was performed to investigate the effect of the ethanol extract of A. koreanum (EEAK) on cholinergic blockade‐induced memory impairment in mice. To evaluate the ameliorating effects of EEAK against scopolamine‐induced memory impairment, mice were orally administered EEAK (25, 50, 100, or 200 mg/kg), and several behavioral tasks, including a passive avoidance task, the Y‐maze, and a novel object recognition task, were employed. Besides, western blot analysis was conducted to examine whether EEAK affected memory‐associated signaling molecules, such as protein kinase B (Akt), Ca 2+ /calmodulin‐dependent protein kinase II (CaMKII), and cAMP response element‐binding protein (CREB). The administration of EEAK (100 or 200 mg/kg, p.o.) significantly ameliorated the scopolamine‐induced cognitive impairment in the passive avoidance task, the Y‐maze, and the novel object recognition task. The phosphorylation levels of both Akt and CaMKII were significantly increased by approximately two‐fold compared with the control group because of the administration of EEAK (100 or 200 mg/kg) ( p  < 0.05). Moreover, the phosphorylation level of CREB was also significantly increased compared with the control group by the administration of EEAK (200 mg/kg) ( p  < 0.05). The present study suggests that EEAK ameliorates the cognitive dysfunction induced by the cholinergic blockade, in part, via several memory‐associated signaling molecules and may hold therapeutic potential against cognitive dysfunction, such as that presented in neurodegenerative diseases, for example, Alzheimer's disease. Copyright © 2017 John Wiley & Sons, Ltd.